886. Positive Bacterial Blood Cultures and Time to Positivity in Children: Should Empiric Antibiotics be Reconsidered Sooner?. (15th December 2022) - Patel, Pratik A; Locsin, Miguel; Xiang, Yijin; Lu, Lydia; Fernandez, Alfred; Jaggi, Preeti
Abstract: Background: Evaluation for bacterial bloodstream infections (BSIs) is often associated with prescribing empiric antibiotics while awaiting blood culture results, typically 48 hours. We examined characteristics associated with positive cultures treated as BSI vs contaminant in children and BSIs associated with prolonged (≥ 24 hours) time-to-positivity (TTP). Methods: In a retrospective study of children (≤ 21 years) at our pediatric healthcare system, we abstracted demographic, clinical, and blood culture data from the electronic medical record for all initial positive bacterial blood cultures from March 2021 to February 2022. We excluded fungi and cultures collected within 14 days of a previous positive. TTP was calculated from time/date of collection to Gram stain report. Host status was categorized as previously healthy, immunocompromised (IC), and chronic condition/s. A BSI was defined as a positive culture treated for ≥ 3 days. BSI cultures were categorized as Gram-positive definite (GPD) pathogens, other Gram-positive (OGP), Gram-negative (GN), or polymicrobial (PM). Characteristics associated with prolonged TTP for BSIs were identified using mixed-effects logistic regression. Results: There were 816 positive cultures identified in 697 children, with 582 (71%) treated as BSIs and 536 of those (92%) positive in < 36 hours. Positive cultures drawn with adequate blood volume, in the setting of fever, severe neutropenia, and from IC children were significantly more likely to be treated as BSIs (all p< 0.05, Table 1). The most common BSI was a GN pathogen (34.2%, Figure 1). Characteristics associated with prolonged TTP were absence of fever and cultures drawn peripherally. Early TTP (< 24 hours) was associated with cultures drawn outpatient and growth of high likelihood pathogenic organisms (GPD, GN, PM) compared to OGP (all p< 0.05). On multivariate analysis, cultures drawn peripherally remained associated with prolonged TTP (p< 0.01), while GPD, GN, and PM cultures remained associated with early TTP (p< 0.01, Table 2). Conclusion: We found that 92% of clinically significant BSIs in children were identified by 36 hours with BSIs with pathogenic organisms (GPD, GN, PM) associated with TTP < 24 hours. Reassessment of the need for antibiotics after 24–36 hours should be considered. Disclosures: Pratik A. Patel, MD, Cardinal Health, Inc: Advisor/Consultant.